The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00113-005-0966-4
|View full text |Cite
|
Sign up to set email alerts
|

Central bone transport system optimizes reconstruction of bone defects

Abstract: In contrast to conventional methods reduced pin tract infections offer better conditions for internal fixation. Control of length and axis can be optimized, immobilization of the patients is reduced, and the comfort of treatment is significantly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…This did not necessarily correlate with when bone regenerate was considered strong enough for frame removal. Other authors have reported similar results[ 24 ]. We therefore advocate early resection of devitalized bone, as this reduces the risk of infection whilst still achieving good results with long transport distances.…”
Section: Discussionsupporting
confidence: 82%
“…This did not necessarily correlate with when bone regenerate was considered strong enough for frame removal. Other authors have reported similar results[ 24 ]. We therefore advocate early resection of devitalized bone, as this reduces the risk of infection whilst still achieving good results with long transport distances.…”
Section: Discussionsupporting
confidence: 82%
“…A study published in 2005 by Baumgart et al similarly noted a higher complication rate (2.3 vs 1.6) and a higher BHI (50.2 vs 40.8) following the development of osteitis. 18 Schmidt et al . (2002) also reported an increased BHI in patients with pre-existing osteitis.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the resulting defect should distinctly be the second priority to minimizing infection risk; as the number of operations, amount of complications, length of hospital stay and BHI are all significantly increased in the case of infection. 18 , 19…”
Section: Discussionmentioning
confidence: 99%
“…In der Fachliteratur finden sich Heilungs-Indices von ca. 26 – 50 Tagen pro cm Defektstrecke 15 , 16 , 17 .…”
Section: Biologische Knochentransplantateunclassified